2021
DOI: 10.3390/cancers13102431
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Map Radiomics in Breast Cancer: Prediction of Metastatic Status

Abstract: Dual-energy CT (DECT) iodine maps enable quantification of iodine concentrations as a marker for tissue vascularization. We investigated whether iodine map radiomic features derived from staging DECT enable prediction of breast cancer metastatic status, and whether textural differences exist between primary breast cancers and metastases. Seventy-seven treatment-naïve patients with biopsy-proven breast cancers were included retrospectively (41 non-metastatic, 36 metastatic). Radiomic features including first-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…This indicates that DESCT-based radiomics has great application prospects in gastric cancer. Previous studies have found that radiomic features derived from dual-energy CT iodine maps are useful in predicting breast cancer metastatic status [ 36 ] and identifying cervical lymph node metastases of thyroid cancer [ 37 ]. In this investigation, iodine-based MD images obtained from DESCT also performed well in predicting GC histologic grade, and the model’s performance was increased when paired with conventional polychromatic images.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that DESCT-based radiomics has great application prospects in gastric cancer. Previous studies have found that radiomic features derived from dual-energy CT iodine maps are useful in predicting breast cancer metastatic status [ 36 ] and identifying cervical lymph node metastases of thyroid cancer [ 37 ]. In this investigation, iodine-based MD images obtained from DESCT also performed well in predicting GC histologic grade, and the model’s performance was increased when paired with conventional polychromatic images.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics features represented tumor heterogeneity and were extracted from the entire ROI; they were not just limited to the biopsy site (17). Previous studies demonstrated that radiomics plays a role in differentiating between primary and metastatic tumors (25)(26)(27)(28)(29). In particular, CT radiomics features combined with positron emission tomography (PET) features can accurately distinguish between primary and metastatic lung cancers (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (25)(26)(27) have demonstrated heterogeneity of tumor perfusion, especially for necrosis and microvessel density (MVD), which are related to aggressive tumor behavior and decreased survival rate, which in turn are prognostic factors for breast cancers. Also, Lenga et al (15) found that iodine map radiomics can serve as an additional tool for assessing the risk of metastasis in breast cancers. Different perfusion and permeability exist in the intratumorally regions of well-oxygenated tissue, hypoxia, or necrosis, which may be reflected by the heterogeneity of iodine maps.…”
Section: Discussionmentioning
confidence: 99%